Dataset for Aquaculture Stakeholder Workshop Characterization (Kenya) - Brako Dompreh, Eric; Manyise, Timothy; Juma, Fredrick (2025)
Data for this study was gathered through participatory workshops conducted with stakeholders across Kenya's diverse landscapes, encompassing the coastal, central, and lake regions. The dataset is further disaggregated by county and sub-county. Relevant traits scored across dimensions: biological, market-driven, environmental, and economic factors. The study identified and ranked challenges encountered: environmental and ecological, socio-economic, technical and infrastructural, policy-related, and regulatory constraints.